2016
DOI: 10.1038/srep31771
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Functional Glomerulus at the Organ Level on a Chip to Mimic Hypertensive Nephropathy

Abstract: Glomerular hypertension is an important factor exacerbating glomerular diseases to end-stage renal diseases because, ultimately, it results in glomerular sclerosis (especially in hypertensive and diabetic nephropathy). The precise mechanism of glomerular sclerosis caused by glomerular hypertension is unclear, due partly to the absence of suitable in vitro or in vivo models capable of mimicking and regulating the complex mechanical forces and/or organ-level disease processes. We developed a “glomerulus-on-a-chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 44 publications
1
123
0
1
Order By: Relevance
“…The most widely modeled component of the kidney is the proximal tubule . Recent development has also attempted to model the kidney glomerulus . However, there has been no attempt to combine various components of kidney into a single OOC system.…”
Section: Current Organ‐on‐a‐chip Platformsmentioning
confidence: 99%
“…The most widely modeled component of the kidney is the proximal tubule . Recent development has also attempted to model the kidney glomerulus . However, there has been no attempt to combine various components of kidney into a single OOC system.…”
Section: Current Organ‐on‐a‐chip Platformsmentioning
confidence: 99%
“…In the past decade, significant progress has been made in generating microfluidic organs-on-a-chip that basically consist of cells cultured on a 2D surface or in 3D tubular structures accompanied by controlled fluid flow throughout the system, either luminal, basal or both. Proof-of-concept studies have showed the successful engineering of a glomerulus-on-a-chip [55,66,67] (Fig. 2).…”
Section: Glomerulus-on-a-chipmentioning
confidence: 99%
“…c Organoids contain multiple nephrons and glomeruli consist of podocytes, endothelial cells, glomerular basement membrane, and parietal epithelial cells, though not fully mature. d Differentiation of podocyte-like cells in 2D or e in a glomerulus-on-a-chip expression levels [66,67]. In these studies, either murine immortalized cells or human primary glomerular tissue were used.…”
Section: Glomerulus-on-a-chipmentioning
confidence: 99%
“…The authors of this study concluded that the native ECM composition contributed to the formation of microvasculature structure. A “glomerulus‐on‐a‐chip” was developed, which comprises two channels lined by opposed layers of glomerular endothelial cells and podocytes . Authors observed that mechanical forces on the cells exerted by the chip plays a crucial role in cellular cytoskeleton rearrangement.…”
Section: Vascularized Organ Chip Modelsmentioning
confidence: 99%